2020
DOI: 10.2147/ott.s265592
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of P-Rex1 in the Regulation of Liver Cancer Cell Proliferation and Migration via HGF/c-Met/Akt Pathway</p>

Abstract: Background: Rho-GTPases and their activators, guanine nucleotide exchange factors (GEFs), are increasingly being recognized as essential mediators of oncogenic signaling. Although it is known that P-Rex1, a member of the Dbl family of GEFs for the Rac small GTPase, contributes to the migration of cancer cells, its exact role in liver cancer and the underlying mechanisms remain unclear. Materials and Methods: Public datasets from the Gene Expression Omnibus database (GEO) and clinical liver cancer samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(49 reference statements)
0
5
2
Order By: Relevance
“…The P-Rex1-dependent regulation of cell-cycle progression and/or cell proliferation has previously been reported, mostly in cancer cells but also in melanoblasts and endothelial cells, and it is often found associated with altered Erk activity and expression levels of cell-cycle regulators [ 16 , 60 , 61 , 62 ]. However, P-Rex1 does not seem to affect these processes universally, as others have reported a lack of effect of P-Rex1 on the proliferation of breast cancer cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The P-Rex1-dependent regulation of cell-cycle progression and/or cell proliferation has previously been reported, mostly in cancer cells but also in melanoblasts and endothelial cells, and it is often found associated with altered Erk activity and expression levels of cell-cycle regulators [ 16 , 60 , 61 , 62 ]. However, P-Rex1 does not seem to affect these processes universally, as others have reported a lack of effect of P-Rex1 on the proliferation of breast cancer cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the role of c‐Met in the procession of HCC. P‐Rex1 promotes proliferation and migration of HCC cells and enhances xenograft tumor growth in vivo by activating the HGF/c‐Met signaling pathway [ 23 ]. The HGF/c‐Met signaling pathway participates in the liver metastasis of colorectal cancer in mice [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol 3,4,5-trisphosphate-dependent Rac exchanger 1 (P-Rex1) is a Rac guanine nucleotide exchange factor (RacGEF) that is upregulated in numerous adult cancers, including breast cancer, prostate cancer, melanoma, and liver cancer (11)(12)(13)(14)(15). It is activated downstream of phosphoinositide 3-kinase (PI3K) and G-protein coupled receptors (GPCRs) to promote activation of Rac (12), which has been implicated in cell migration, a process that is critical for tumor metastasis (13).…”
Section: Introductionmentioning
confidence: 99%
“…It is activated downstream of phosphoinositide 3-kinase (PI3K) and G-protein coupled receptors (GPCRs) to promote activation of Rac (12), which has been implicated in cell migration, a process that is critical for tumor metastasis (13). Although P-Rex1 demonstrates negligible protein expression in most benign tissues (13)(14)(15), it is thought to stimulate numerous aspects of oncogenesis, including migration, invasion, and metastasis in various malignancies (13,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%